The Freedom to Determine the Choice to Have or not have Children - Mantaru, Richard; Martoko, Joko; Haris, Andi (PT. Riset Press International, 2023)
The decision to choose childfree in household life cannot be separated from the role of husband and wife. The method used in this research is qualitative, with a comparative approach, namely comparing two points of view, namely according to classical and contemporary Islamic scholars. While the type of research used is Library Research, in the sense that all data sources come from written materials related to the topics discussed. The results of the research show that the classical ulema’s do not forbid a husband and wife who agree not to have children (offspring). Because this is confirmed by 'Azl, which is legally permitted by Imam Ghazali, as well as contemporary scholars also allow it if husband and wife agree because of certain benefits. So childfree is not included in the prohibited acts, because every married couple has the right to plan and manage household life including having children.